Biogenic emissions by oak trees common to Mediterranean ecosystems (Environmental Monitoring and Assessment, 1998)
An inventory describing the fluxes of volatile organic compounds (VOCs), isoprene and monoterpenes, and other VOCs (OVOCs) from the biosphere to the atmosphere, has been constructed within the framework of the ESCOMPTE project (fiEld experimentS to COnstrain Models of atmospheric Pollution and Transport of Emissions). The area concerned, located around Berre-Marseilles, is a Mediterranean region frequently subject to high ozone concentrations. The inventory has been developed using a fine scale land use database for the year 1999, forest composition statistics, emission potentials from individual plant species, biomass distribution, temperature and light intensity. The seasonal variations in emission potentials and biomass were also taken into account. Hourly meteorological data for 1999 were calculated from ALADIN data and these were used to predict the hourly isoprene, monoterpene and OVOC fluxes for the area on a 1 km × 1 km spatial grid. Estimates of annual biogenic isoprene, monoterpene and OVOC fluxes for the reference year 1999 were 20.6, 38.9 and 13.3 kt, respectively, Quercus pubescens, Quercus ilex, Pinus halepensis and garrigue vegetation are the dominant emitting species of the area. VOC emissions from vegetation in this region contribute approximately 94% to the NMVOC (non-methane volatile organic compounds) of natural origin and are of the same order of magnitude as NMVOC emissions from anthropogenic sources. These results complete the global ESCOMPTE database needed to make an efficient strategy for tropospheric ozone reduction policy.

EMISSION OF SHORT CHAINED ORGANIC ACIDS , ALDEHYDES AND MONOTERPENES FROM QUERCUS ILEX L . AND PINUS PINEA L . IN RELATION TO PHYSIOLOGICAL ACTIVITIES , CARBON BUDGET AND EMISSION ALGORITHMS (Atmospheric Environment, 1997)
We report on the emission of monoterpenes, short-chained organic acids and aldehydes from Mediterranean oak (Quercus ilex L.) and pine (Pinus pinea L.). All studies were done with dynamic cuvettes enclosing intact branches at the top of the canopy flushed with ambient air. Daily trends are compared with the photosynthetic active radiation (PAR), leaf temperature and the physiological activities of the enclosed branches, i.e. assimilation and transpiration, with special attention on the carbon budget. Oak emits monoterpenes in high amounts, up to 2% of the assimilated carbon. As compared with monoterpenes, short-chained organic acids and aldehydes are of minor importance for oak. However, on a leaf dry-weight basis equal amounts of acids and aldehydes are released from oak and pine. As pine emitted only low amounts of terpenes (below 0.2% of the assimilated carbon) the release of terpenes and oxygenated compounds is of equal importance for this species. A comparison of a modelled light and temperature driven emission with the observed volatile organic compounds (VOC) emissions showed good agreement for monoterpenes as well as for organic acids emitted in the case of oak. For pine only the release of acids showed an adequate relation to the algorithm data, whereas the terpene emissions seemed to be dominated by temperature effects

EMISSION OF MONOTERPENES AND ISOPRENE FROM A MEDITERRANEAN OAK SPECIES QUERCUS ILEX L. MEASURED WITHIN THE BEMA (BIOGENIC EMISSIONS IN THE MEDITERRANEAN AREA) PROJECT EMISSIONS IN THE M E D I T E (Atmospheric Environment, 1996)
We report on some results of our studies of monoterpene and isoprene emissions and the physiological activities of an oak species (Quercus ilex L.) under the Mediterranean climatic conditions found at Castel Porziano (Rome) in June 1993. The oak species Quercus ilex L. was found to emit mainly monoterpenes in high amounts. Isoprene emissions were negligible. Diel cycles of monoterpene emissions showed correlation with light and the diel behaviour of photosynthetic CO2 assimilation, transpiration and stomatal corductance. Temperature dependence seemed to be of minor importance.